Infinite Trigonometric Sums Part 1

Geometry Level 3

The infinite sum below when x = π 6 x=\frac{\pi}{6} can be expressed as a b \frac{a}{b} , where a a and b b are coprime positive integers. What is the value of a 2 + b 2 a^{2}+b^{2} ?

sin x 2 sin 2 x + 3 sin 3 x 4 sin 4 x + 5 sin 5 x 6 sin 6 x + \sin x - 2 \sin^{2} x + 3 \sin^{3} x - 4 \sin^{4} x + 5 \sin^{5} x - 6 \sin^{6} x +\ldots


The answer is 85.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Oliver Bel
Mar 31, 2014

The required sum is

S = n = 1 ( 1 ) n 1 n 2 n = 1 2 n = 1 n ( 1 2 ) n 1 S=\sum \limits_{n\mathop=1}^{\infty}\frac{(-1)^{n-1}n}{2^n} =\frac{1}{2}\sum \limits_{n\mathop=1}^{\infty}n\left(-\frac{1}{2}\right)^{n-1}

By differentiating the formula n = 1 x n = x 1 x \sum \limits_{n\mathop=1}^{\infty}x^n=\frac{x}{1-x} we find

n = 1 n x n 1 = 1 ( x 1 ) 2 \sum \limits_{n\mathop=1}^{\infty}nx^{n-1}=\frac{1}{(x-1)^2}

Substituting x = 1 2 x=-\frac{1}{2} we can deduce

S = 2 9 S=\frac{2}{9} so a 2 + b 2 = 85 a^2+b^2=\boxed{85} .

Daniel Liu
Mar 31, 2014

A slightly different way than Oliver:

The required sum is S = i = 1 i ( 1 2 ) i S=\displaystyle\sum_{i=1}^{\infty}-i\left(-\dfrac{1}{2}\right)^i

Note that 1 2 S = i = 1 i ( 1 2 ) i + 1 -\dfrac{1}{2}S=\displaystyle\sum_{i=1}^{\infty}-i\left(-\dfrac{1}{2}\right)^{i+1}

Subtracting this second equation from the first, we arrive at the conclusion that 3 2 S = ( i = 1 i ( 1 2 ) i ) ( i = 1 i ( 1 2 ) i + 1 ) = i = 1 ( 1 2 ) i = 1 2 1 ( 1 2 ) = 1 3 \begin{aligned}\dfrac{3}{2}S&=\left(\displaystyle\sum_{i=1}^{\infty}-i\left(-\dfrac{1}{2}\right)^i\right)-\left(\displaystyle\sum_{i=1}^{\infty}-i\left(-\dfrac{1}{2}\right)^{i+1}\right)\\ &= \displaystyle\sum_{i=1}^{\infty}-\left(-\dfrac{1}{2}\right)^i\\ &= \dfrac{\frac{1}{2}}{1-(-\frac{1}{2})}\\ &= \dfrac{1}{3}\end{aligned}

Since 3 2 S = 1 3 \dfrac{3}{2}S=\dfrac{1}{3} , then S = 2 9 S=\dfrac{2}{9} and our desired answer is 2 + 9 = 11 2+9=\boxed{11} .

Small typo in the end it should be a 2 + b 2 = 85 a^2 +b^2=85 BTW awesome solution

Milun Moghe - 7 years, 2 months ago

This was Arithmetico Geometric Sequence

jatin yadav - 7 years, 2 months ago

Once you subtract both of them could you please explain how you got the 2nd step which is i = 1 \displaystyle \sum_{i=1}^\infty -( 1 2 \frac {-1}{2} ) i ^i

Thank you.

Vishwa Shah - 7 years, 1 month ago
Michael Tong
Apr 3, 2014

Clearly sin π / 6 = 1 2 \sin{\pi / 6} = \frac{1}{2} , so substitute that into the formula.

We have an infinite geometric series of infinite geometric series. In particular,

S 1 = 1 2 1 4 + 1 8 = 1 / 2 3 / 2 S_1 = \frac 12 - \frac 14 + \frac 18 - \dots = \frac{1/2}{3/2}

S 2 = 1 4 + 1 8 = 1 / 4 3 / 2 S_2 = - \frac 14 + \frac 18 - \dots = -\frac{1/4}{3/2}

and so forth.

Thus the required sum is S = 2 3 ( 1 2 1 4 + 1 8 ) = 2 3 ( 1 / 2 3 / 2 ) = 2 9 S = \frac23 \left(\frac 12 - \frac 14 + \frac 18 \dots \right) = \frac23 \left( \frac{1/2}{3/2} \right) = \frac 29

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...